2023
DOI: 10.3390/diagnostics13061005
|View full text |Cite
|
Sign up to set email alerts
|

Masked Hypertension and Exaggerated Blood Pressure Response to Exercise: A Review and Meta-Analysis

Abstract: Aim: Whether exaggerated blood pressure response (EBPR) to exercise represents a marker of masked hypertension (MH) in individuals with no prior history of hypertension is still unclear. We investigated this issue through a review and a meta-analysis of studies providing data on this association in normotensive individuals undergone both to dynamic or static exercise and to 24 h blood pressure monitoring (ABPM). Design: A systematic search was performed using Pub-Med, OVID, EMBASE, and Cochrane library databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Fourth, middle-aged long-distance runners must check their exercise blood pressure at least once every year via an exercise stress test. The recent meta-analysis by Cuspidi et al [139] reported that individuals with EIH face an increased risk of masked hypertension. This finding suggests that an exaggerated blood pressure response to exercise could serve as a forewarning of cardiovascular risk associated with blood pressure, regardless of any prior diagnosis of heart disease [140].…”
Section: Interventions For Prevention Of Scd In Runners With Eihmentioning
confidence: 99%
“…Fourth, middle-aged long-distance runners must check their exercise blood pressure at least once every year via an exercise stress test. The recent meta-analysis by Cuspidi et al [139] reported that individuals with EIH face an increased risk of masked hypertension. This finding suggests that an exaggerated blood pressure response to exercise could serve as a forewarning of cardiovascular risk associated with blood pressure, regardless of any prior diagnosis of heart disease [140].…”
Section: Interventions For Prevention Of Scd In Runners With Eihmentioning
confidence: 99%